Communication technology and post-divorce coparenting - Ganong, Lawrence H.; Coleman, Marilyn; Feistman, Richard; Jamison, Tyler; Markham, Melinda S. (My University, 2012)
Divorced individuals who share parenting responsibilities have to figure out ways to work together to raise their children. The purpose of this qualitative study of 49 divorced coparents was to examine how they used technology (e.g., cell phones, computers) to communicate. For parents in effective coparenting relationships, communication technologies made it easier for them to plan and make conjoint decisions about their children while living apart. Communication technology, however, did not necessarily make coparenting easier if parents were contentious. Contentious parents used communication technologies as tools to: (a) reduce conflicts, (b) withhold information, (c) limit the ability of the coparent to have input into child-rearing decisions, and (d) try to influence the behavior of the coparent.
Keywords: Communication; Coparenting; Divorce; Technology